Prognostic factors after hepatic resection for the single hepatocellular carcinoma larger than 5 cm - Noh, Ji Hyun (Ann Surg Treat Res, 2016)
PURPOSE: This study aimed to determine which factors affect the prognosis of hepatectomy for hepatocellular carcinoma (HCC) larger than 5 cm, including the prognostic difference between tumor sizes from 5–10 cm and larger than 10 cm. METHODS: The medical records of 114 patients who underwent hepatectomy for single HCC larger than 5 cm were reviewed and analyzed retrospectively. RESULTS: In the analysis of the entire cohort of 114 patients, the 5-year overall and diseases-free survival rates were 50% and 29%, respectively. In a comparison of survival rates between groups, tumor sizes of 5 to 10 cm and larger than 10 cm, the overall and disease-free survival rates were not significantly different, respectively (54% vs. 41%, P = 0.433 and 33% vs. 23%, P = 0.083). On multivariate analysis, positive hepatitis B, high prothrombin induced by vitamin K absence or antagonist-II levels over 200 mIU/mL, and vascular invasion (micro- and macrovascular invasion) were independent prognostic factors for recurrence after hepatic resection. However, tumor size larger than 10 cm was not significant for recurrence after resection. CONCLUSION: This study shows that surgical resection of solitary HCC larger than 5 cm showed favorable overall survival. And there is no survival difference with tumors between 5–10 cm and larger than 10 cm.